The potentials and challenges of artificial intelligence in Kazakhstan’s modern transformation (Journal of Philosophy Culture and Political Science, 2025)
The rapid advancement of digital technologies globally is reshaping societal structures and influencing new trends that deviate from traditional developmental paths. As artificial intelligence (AI) emerges as a pivotal innovation within this technological revolution, its integration across various domains has highlighted both new opportunities and pressing challenges. Initially confined to technical disciplines, AI now prompts public discourse on potential societal impacts, particularly in the humanities where ethical transformations raise concerns. The Fourth Industrial Revolution, particularly AI, is transforming modern life, especially the labor market. AI is automating routine tasks, enhancing efficiency but also displacing jobs. While AI is expected to create new opportunities, its rapid integration raises ethical and legal concerns, including data privacy, ownership, and algorithmic bias. As high-skilled jobs grow, educational institutions must prepare individuals with adaptive skills. Emphasizing “AI literacy” and lifelong learning is crucial for equipping people to thrive in an AI-driven world, ensuring social resilience and a balanced transition. This article examines the scientific discourse surrounding these issues, analyzing the core ethical dilemmas in a transformed society - a discourse that holds particular relevance for the swiftly evolving technological landscape of Kazakhstan.Keywords: society, transformation, artificial intelligence, Kazakhstan, new opportunities and challenges, ethical dilemmas.